2021
DOI: 10.3390/su131910972
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Air Quality on Inbound Tourist Arrivals over China Based on Grey Relational Analysis

Abstract: Air pollution has a significant impact on tourism; however, research in this area is still limited. In this study, we applied grey relational analysis to panel data from 31 provinces in China and evaluated the relationship between air quality and inbound tourist arrivals. The study focused on provincial-level disparities for the different key air quality evaluation standards during 2009–2012 and 2013–2019. For instance, we considered PM10, SO2, NO2 and the excellent and good ratings of Air Pollution Index (API… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…When formulating a reasonable educational information resource construction policy, it can serve as a guide for decision-making in areas such as co-construction and sharing of high-quality educational information resources, improving educational resource utilization, and establishing regional information core resources. In the traditional centralized control mode, information servers in one or more regions search for grid resource instances of specific university information resources, i.e., the local university resource information database registers local university resource information with the regional university information server, and grid users register local university resource information with the regional university information server [28].…”
Section: E Mechanism Of Optimal Allocation Of Regional Higher Educati...mentioning
confidence: 99%
“…When formulating a reasonable educational information resource construction policy, it can serve as a guide for decision-making in areas such as co-construction and sharing of high-quality educational information resources, improving educational resource utilization, and establishing regional information core resources. In the traditional centralized control mode, information servers in one or more regions search for grid resource instances of specific university information resources, i.e., the local university resource information database registers local university resource information with the regional university information server, and grid users register local university resource information with the regional university information server [28].…”
Section: E Mechanism Of Optimal Allocation Of Regional Higher Educati...mentioning
confidence: 99%
“…In order to objectively evaluate the environmental quality of the urban environment and understand the actual situation of urban environmental quality, the above six basic pollutant indexes can be used as evaluation factors. Based on the environmental quality standards in Table 3, the evaluation standard set and weight set of each pollution factor are established, and then the fuzzy comprehensive evaluation method is used to objectively and comprehensively evaluate the urban atmospheric environmental quality [24,25].…”
Section: Evaluation Modelmentioning
confidence: 99%
“…Relevant studies are as follows. Zhang et al [4] applied gray correlation analysis to panel data of Chinese provinces and assessed the connections between air quality and the volume of incoming tourists. They found that ambient air quality had a noteworthy and positive impact on inbound tourists.…”
Section: Introductionmentioning
confidence: 99%